PERAN GURU DALAM MENINGKATKAN SIKAP NASIONALISME DALAM PEMBELAJARAN SEJARAH SISWA KELAS XI IPS SMA NEGERI 9 PEKANBARU - Ayu Fatmasari; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The attitude of nationalism among students today is classified as apprehensive, such as student brawls, not being solemn in attending ceremonies, not memorizing nationalist songs. This study aims to determine the role of teachers in improving attitudes of nationalism in learning history for students of class XI IPS SMA Negeri 9 Pekanbaru. This study used a qualitative method by taking research at SMA Negeri 9 Pekanbaru. The informants in this study were history teachers and students. Data collection techniques using interviews, observation and documentation. The data analysis used in this research is qualitative data analysis. The results of this study are as follows: the attitude of nationalism among the XI IPS grade students of SMA Negeri 9 Pekanbaru in terms of being proud to be an Indonesian nation, willing to sacrifice for the nation, love the country and the nation, accept diversity, pride in diverse cultures, appreciate heroic services. the whole is already growing among students. The role of the teacher in increasing the attitude of nationalism in the history learning of class XI IPS students at SMA Negeri 9 Pekanbaru is to always guide and provide moral messages to students, provide nationalism values by telling stories of heroes in the teaching and learning process, using various methods so that students not easily bored, and this method is considered effective. Teachers 'obstacles in improving students' attitudes of nationalism are factors of different family backgrounds, school environmental factors and factors of globalization or the use of the internet that have a negative impact. The effort made by the teacher is to approach students so that they always leave actions that can damage student morals and provide religious values in between learning.Key Words: Teachers, Nationalism Attitudes, History, Students